2017
DOI: 10.1016/j.envpol.2017.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the rate of perfluorooctanoic acid degradation in laccase-mediator systems: The impact of metal ions

Abstract: This study investigated the factors that regulated the degradation of perfluorooctanoic acid (PFOA) in laccase-catalyzed oxidative humification reactions with 1hydroxybenzotriazole (HBT) as a mediator. The reaction rates were examined under conditions with key factors varied, including initial PFOA concentrations, laccase and HBT dosages, and the ionic contents of the reaction solutions. The PFOA degradation followed pseudo-first order kinetics, and the rate constants (k) were similar for the high (100 μmole L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
3
21
0
Order By: Relevance
“…and Penicillium sp., respectively. (Desai & Nityanand, 2011) and may be able to transform PFOA (Luo et al, 2015;Luo et al, 2017). These previous reports and the ability of the six fungal isolates to tolerate high PFOA and PFOS concentrations suggest that these isolates may be able to transform fluorinated substances.…”
Section: Identification Of Fungal Isolatessupporting
confidence: 60%
See 1 more Smart Citation
“…and Penicillium sp., respectively. (Desai & Nityanand, 2011) and may be able to transform PFOA (Luo et al, 2015;Luo et al, 2017). These previous reports and the ability of the six fungal isolates to tolerate high PFOA and PFOS concentrations suggest that these isolates may be able to transform fluorinated substances.…”
Section: Identification Of Fungal Isolatessupporting
confidence: 60%
“…Although few studies have reported the biotransformation of organic pollutants by species in Lachnum sp. , one report demonstrated that Lachnum spartinae could produce laccase, an extracellular fungal enzyme known to biotransform many environmental pollutants (Desai & Nityanand, ) and may be able to transform PFOA (Luo et al., ; Luo et al., ). These previous reports and the ability of the six fungal isolates to tolerate high PFOA and PFOS concentrations suggest that these isolates may be able to transform fluorinated substances.…”
Section: Resultsmentioning
confidence: 99%
“…The reactivity of laccase with biolignin is explained by the chemical structure of the latter, which resists degradation during the first stage at 30 days and degrades during the second stage at 120 days, as confirmed by Albrecht et al [31]. The biochemistry of laccase has a broad class of phenoloxidase in soils [60]. It is a multicopper, and it can oxidize organic and inorganic compounds besides biolignin, also with compounds that may be present (including mono-, di-, and polyphenols, aminophenols, methoxy phenols, etc.)…”
Section: Discussionmentioning
confidence: 82%
“…According to Sinsabaugh [60], the increase in laccase activity observed during the first stage is marked by the conditions pH: 7.39-7.62, ω%: 20-25, and T • C: 13-14, and in the second stage is marked by pH 7.80-7.62, ω% 9-11, and T • C 35-38. The values < 0.05.10 −2 IU/g reported by Fujii et al [33] for a forest soil (humid environment) are lower than those observed in our trial.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation